The Role of Fintech in Enhancing Financial Inclusion Through Point of Sale (POS) Business in Kano State–Nigeria - Nura Musa (International Journal of Sustainable Business, Management and Accounting, 2025)
Background of Study: This study explores how financial technology (Fintech) contributes to enhancing financial inclusion, particularly through the operation of Point of Sale (POS) businesses in Kano State, Nigeria. In a context where access to traditional banking remains limited, POS businesses provide a practical alternative to financial services. Aims and Scope of Paper: The research focuses on evaluating the perceived benefits, the level of adoption, and the challenges associated with Fintech solutions among POS business owners in Kano State. It aims to understand the role Fintech plays in supporting financial inclusion in underserved regions. Methods: The study utilizes a survey approach with data collected from 80 SME (POS) owners. Quantitative analysis was conducted to assess the relationships among Fintech usage, benefits, and challenges. Result: The findings reveal that Fintech significantly enhances financial inclusion via POS businesses by facilitating efficient transactions and improving access to financial services. However, several challenges persist, including infrastructural deficiencies, gaps in digital literacy, and concerns about cybersecurity. Conclusion: Despite notable barriers, Fintech remains a critical enabler of financial inclusion in Kano State. The study recommends targeted training for POS operators, improvement of digital infrastructure, and the development of tailored Fintech solutions to meet the specific needs of small businesses.